Addressing the Eviction Crisis and Housing Instability Through Mediation - Karen Tokarz; Samuel Hoff Stragand; Michael Geigerman; Wolf Smith (Washington University Journal of Law & Policy, 2020)
The United States faces a staggering eviction crisis. St. Louis City and St. Louis County illustrate the numbers found in major cities throughout the country. The high number of eviction lawsuits filed in these areas present opportunities to address evictions outside of litigation, specifically through housing court mediation. The Mediation Project provides free mediation services for the pro se housing dockets in both St. Louis City and St. Louis County Circuit Courts. Using the Mediation Project as an example, this Article proposes that mediation is one of the cheapest, easiest, and most effective ways to intervene to decrease housing evictions and promote housing stability.
Keywords: dispute resolution; alternative dispute resolution; ADR; mediation; Mediation Project; eviction; housing instability